2012
DOI: 10.1097/mog.0b013e3283505a3b
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine derivatives

Abstract: A number of therapeutic effects possibly come from the interaction of carnitine and its derivatives with the elements of cellular membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 89 publications
1
31
0
2
Order By: Relevance
“…Brain acyl-carnitines can function in synthesizing lipids, altering and stabilizing membrane composition, improving mitochondrial function, increasing antioxidant activity, and enhancing cholinergic neurotransmission [32]. A decreased activity of CAT has been measured in temporal cortex of AD patients [33] (and in our analysis as well - Figure 2), and it has been demonstrated that acetyl-carnitine administration can improve the cognitive performance in patients with mild AD [34].…”
Section: Resultssupporting
confidence: 64%
“…Brain acyl-carnitines can function in synthesizing lipids, altering and stabilizing membrane composition, improving mitochondrial function, increasing antioxidant activity, and enhancing cholinergic neurotransmission [32]. A decreased activity of CAT has been measured in temporal cortex of AD patients [33] (and in our analysis as well - Figure 2), and it has been demonstrated that acetyl-carnitine administration can improve the cognitive performance in patients with mild AD [34].…”
Section: Resultssupporting
confidence: 64%
“…Although most of colorectal patient were able to work, lower levels of productivity, lower work ability and reduced job retention have been reported. An adequate supportive therapy of fatigue [22][23][24] could increase work productivity and health-related quality of life. Future studies are needed to investigate the relation among job, cancer, and related cancer treatment, and develop innovative approaches at the workplace to address these areas realistically and head on.…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine is synthesized from the essential aminoacids lysine and methionine in kidney, liver and brain (7). L-carnitine, acetyl-L-carnitine and various carnitine enzymes play a relevant role in cellular energy production (8) being involved in the carriage of long-chain fatty acids into the mitochondrial matrix for beta oxidation (9). Previous studies showed that carnitine and its derivatives reduce depression, both physical and mental fatigue, improves cognitive functions and quality of life (10, 11).…”
Section: Introductionmentioning
confidence: 99%